2023
DOI: 10.1037/per0000600
|View full text |Cite
|
Sign up to set email alerts
|

Personality disorders research and social decontextualization: What it means to be a minoritized human.

Abstract: Models of personality disorders have overwhelmingly developed in a socially decontextualized manner. Some historical models of personality pathology formally embraced the interactions between the individual and their environment. However, the field of personality disorder theory, research, and treatment has evolved in a manner that situates dysfunction within intraindividual deficiency processes. By doing so the field limits its applicability to populations that do not represent the norm in clinical psychologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 80 publications
0
16
0
Order By: Relevance
“…SGM individuals contend with elevated rejection sensitivity as a consequence of repeated exposure to rejection due to one’s sexual orientation and/or gender expression (Feinstein, 2020). If attention-seeking behaviors in response to the threat of rejection present a maladaptive emotion-regulation strategy in SGM individuals (Rodriguez-Seijas et al, 2022), this could explain the observed pattern of results. In addition, stereotypes about SGM individuals as being attention-seeking abound and might be internalized by SGM persons (Boysen et al, 2011), non-SGM persons (Boysen et al, 2006, 2011), and even clinical care providers (Boysen et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…SGM individuals contend with elevated rejection sensitivity as a consequence of repeated exposure to rejection due to one’s sexual orientation and/or gender expression (Feinstein, 2020). If attention-seeking behaviors in response to the threat of rejection present a maladaptive emotion-regulation strategy in SGM individuals (Rodriguez-Seijas et al, 2022), this could explain the observed pattern of results. In addition, stereotypes about SGM individuals as being attention-seeking abound and might be internalized by SGM persons (Boysen et al, 2011), non-SGM persons (Boysen et al, 2006, 2011), and even clinical care providers (Boysen et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the many environmental factors that can influence self-reported symptoms and maladaptive traits in SGM populations is critical to the development and validation of maladaptive trait measures. Personality disorder disparities in SGM groups may emerge due to processes other than intraindividual deficits, such as environmental and structural factors that systematically affect SGM individuals as well as their reporting styles (Cano et al, 2022; Cardona et al, 2022; Rodriguez-Seijas et al, 2022). External processes that are nonspecific to personality disorders such as minority stress or structural stigma (e.g., Hatzenbuehler, 2009; Pachankis et al, 2014, 2021) may inflate maladaptive trait endorsement among SGMs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, that little research on the HiTOP model—from which the disinhibited externalizing spectrum is derived—has included sexual-minority participants or appreciated the sociocultural context in which sexual-minority participants exist makes it unclear whether the model is indeed applicable in the same way for sexual-minority populations as it might be for heterosexual populations. Recent scholarship has outlined how the conceptualization of personality pathology, to which the HiTOP domains bear striking resemblance (Markon, 2010; Wright et al, 2012), is misaligned with evidence-based ways of understanding the psychosocial needs of sexual- and gender-minority populations (Rodriguez-Seijas et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, psychosocial and psychiatric health among sexual-minority populations cannot be understood solely using intraindividual models and assumptions. We direct interested readers to one recent publication that expands on the ways that traditional conceptualization of psychopathology—in this case, personality pathology—is not always aligned with understanding psychosocial health of sexual-minority populations ( Rodriguez-Seijas et al, 2022).…”
mentioning
confidence: 99%